The Relationship of Library Satisfaction with Reference Collection Services: a Study in a Higher College Library - Erwina, Wina; Sandy, Gitania Aulia; Fauziyah, Helen Nur; Effendy, Meuthia Salsya (Universitas Pendidikan Indonesia, 2024)
Reference services are an important form of service which has the function of providing answers, guidance and direction to readers in finding the right library materials. The Knowledge Management Center, especially the Padjadjaran University Library Service as a university library, has a role in meeting information needs so the presence of reference services is very necessary to help students. So this research has the aim of finding out the relationship between user satisfaction with reference service librarians, reference collections and reference service facilities at the Padjadjaran University Library Service Knowledge Management Center. In its implementation, this research used a quantitative approach with a survey method. Researchers carried out research at the Padjadjaran University Library Services Knowledge Management Center. The data collection technique in this research is through distributing questionnaires and interviews using probability sampling or what is known as simple random sampling as a sampling technique. The results of this research are that there is a significant relationship with several indicators, namely speed of purchasing services, skills, completeness of collection, type of collection, and appearance on the website. Researchers used Pearson Product Moment analysis and Chi-square analysis in this research. Meanwhile, the theory used as an indicator of user satisfaction is the DeLone McLean theory called the IS Success Model.